Perceived Social Interaction Anxiety as a Predictor of Self-Harm Urge: Self-Acceptance as a Shield Among University Students - Agesin, Emmanuel Bamikole; Balogun, Anthony Gbenro; Oluwabukolami, Adamson Favour (Happiness: Journal of Psychology and Islamic Science, 2026)
This study focused on the mediating function of self-acceptance in the relationship between self-harm urges and social interaction anxiety among Nigerian undergraduates. Although anxiety related to social interactions has been identified as a risk factor for self-harming behavior, little research has examined this relationship in non-Western contexts. The study investigated university students in Nigeria to close this gap. 428 undergraduate students from the University of Ilorin in Kwara State, 112 males and 316 females, participated. They were selected using purposeful and convenient sampling methods. Strongly reliable standardized self-report measures were used to measure the urge to harm oneself (α =.96), social interaction anxiety (α =.92), and self-acceptance (α =.80). Regression and mediation analyses were used in the cross-sectional design to test the hypotheses. The results showed that self-harm urges were significantly predicted by social interaction anxiety (β =.234, t = 4.667, p <.01). Additionally, this relationship was found to be partially mediated by self-acceptance (β =.169, t = 3.454, p <.01). This lends credence to a dual pathway model, which demonstrates how social interaction anxiety both directly and indirectly influences self-harm by lowering self-acceptance. By bringing this dynamic to light in a non-Western cultural setting and bringing attention to undergraduates' psychological susceptibility, the study advances our understanding.